Organoleptic Tests on Processed Products of Meatballs, Tofu Meatballs, Dumplings, and Herbal Drinks - Nunuk Helilusiatiningsih; Navita Maharani; Nastiti Winahyu (International Journal of Integrative Research, 2023)
This study aims to analyze the level of consumer preference for processed meatball products, meatball tofu, and herbal drinks produced on a household scale. This research was carried out in 2 stages, the first was the production stage and the second was the organoleptic test stage with the hedonic method or consumer preference level analysis. The importance of this research is to find out the results of food processing that can be accepted by consumers and how much the consumer's preference level is, as well as to measure the response of food quality to the product. Processed products tested in this study were meatballs, meatball tofu, dumplings and herbal drinks. The product parameters tested in this study include general appearance, color, taste, texture, and aroma. The results showed that processed meatball products, meatball tofu, dumplings and herbal drinks produced on a household scale were generally well received and liked by consumers. However, there are several parameters such as taste and aroma that still need improvement. Improvements were made to improve and increase consumer preferences for processed products such as meatballs, meatball tofu, dumplings and herbal drinks.